Dental vulnerability scale in primary health care: evidence of content and structure internal validity - Danielle da Costa da Palacio; Flavio Rebustini; Daniele Boina de Oliveira; João Peres Neto; Wander Barbieri; Thais Paragis Sanchez; Ana Carolina Cintra Nunes Mafra; Daiana Bonfim; Camila Nascimento Monteiro; Valmir Vanderlei Gomes Filho; Danielle Viana Ribeiro; Leandro Marsico Loschiavo; et al. (BMC, 2021)
Abstract Background Access to oral health services remains a challenge in the Brazilian healthcare system, especially in the primary health care setting, where the use of a risk stratification tool that could identify individuals with higher dental vulnerability would be extremely valuable. However, there literature on this theme is scarce, and there is no validated instrument in Brazil that is capable of measuring dental vulnerability. Hence, this psychometric study aimed at the development and evaluation of content and internal structure validity of the Dental Vulnerability Scale for Primary Health Care (PHC). Methods The items were developed based on a qualitative exploratory analysis. A total of 172 items were prepared and submitted to a panel of specialists, with content validity analyzed with the Content Validity Ratio (CVR), resulting in an the initial version of the instrument composed by 41 items. Internal structure validity was analyzed by Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and by applying 3 reliability indicators (Cronbach's Alpha, McDonald's Omega and Greatest Lower Bound - GBL), with a sample of 1227 individuals. Results The final configuration indicated a scale of 15 items divided into 4 dimensions (overall health, oral health, infrastructure, and healthcare services) with explained variance of 72.11%. The factor loads varied from 0.37 to 0.96. The model adjustment indices were set at × 2/df(51) = 3.23, NNFI = 0.95, CFI = 0.98, GFI = 0.96, AGFI = 0.97, RMSEA = 0.04 and RMSR = 0.03. Conclusion DVS presented satisfactory evidence of validity, indicating its suitability to be used by healthcare professionals, students and managers to plan oral health actions and services at PHC.